Redox-Active Water-Soluble Low-Weight and Polymer-Based Anolytes Containing Tetrazine Groups: Synthesis and Electrochemical Characterization - Kozhunova, Elena Yu; Sentyurin, Vyacheslav V.; Inozemtseva, Alina I.; Nikolenko, Anatoly D.; Khokhlov, Alexei R.; Magdesieva, Tatiana V. (Polymers, 2025)
Polymer-based aqueous redox flow batteries (RFBs) are attracting increasing attention as a promising next-generation energy storage technology due to their potential for low cost and environmental friendliness. The search for new redox-active organic compounds for incorporation into polymer materials is ongoing, with anolyte-type compounds in high demand. In response to this need, we have synthesized and tested a range of new water-soluble redox-active s-tetrazine derivatives, including both low molecular weight compounds and polymers with different architectures. S-tetrazines are some of the smallest organic molecules that can undergo a reversible two-electron reduction in protic media, making them a promising candidate for anolyte applications. We have successfully modified linear polyacrylic acid and poly(N-isopropylacrylamide-co-acrylic acid) microgels with pendent 1,2,4,5-tetrazine groups. Electrochemical testing has shown that the new tetrazine-containing monomers and, importantly, the water-soluble redox polymers, both linear and microgel, demonstrate the chemical reversibility of the reduction process in an aqueous solution containing acetate buffer. This expands the range of water-soluble anodic materials suitable for water-based organic RFBs. The reduction potential value can be adjusted by changing the substituents in the tetrazine core. It is also worth noting that the choice of electrode material plays an important role in the kinetics of the tetrazine reaction: the use of carbon electrodes is particularly beneficial.